Current status and impact (2004-2015) of indigenous ungulate herbivory on the vegetation of Sanbona Wildlife Reserve in the Little Karoo - Vorster, Liesl (Plant Conservation Unit (PCU), 2017)
Game farming is becoming more popular in southern Africa and the introduction of large indigenous ungulates into confined enclosed areas could alter plant communities and ecosystem processes. This is of particular concern in semi-arid rangelands of the Succulent Karoo where the evolutionary history of grazing is not clear and the compatibility of large herbivores in confined areas remains to be demonstrated. The establishment of Sanbona Wildlife Reserve, a 54 000 hectare private game reserve in the Little Karoo, which converted from livestock farming to game farming, allows an opportunity to study the vegetation dynamics in a confined plant-herbivore system. This study investigates the current community structure and the changes in the floral composition and vegetation structure of enclosed and comparable sites subjected to grazing by large herbivores after twelve years (2004-2015). It also determines the relative effect of grazing and rainfall on the observed patterns. Finally, the implications of these findings for management are discussed. Data from drop-point surveys in fenced (exclosure) and unfenced (grazed) plots in the dominant vegetation types as well as annual and seasonal rainfall totals, stocking rates of herbivores and annual game census information, were analysed. These were used in multivariate ordination techniques, regressions and linear mixed-effects models to determine the communities and their relationship with herbivory and rainfall over time and identify a set of indicator species. The annual game census information was used to determine areas of herbivore preference or 'hotspots' and for the identification of highly-utilised areas. Cluster analysis, using the flexible beta method in PC-Ord, was used to determine the current plant communities. Non-metric multidimensional scaling ordination (NMS) was used to determine the relationship of these communities with the environmental variables and illustrate the trajectories in floristic data. Species were also assigned to plant growth forms and examined as communities and growth form types. The Bray-Curtis distance measures were used to investigate the difference between each treatment over time, within each vegetation community and between treatments. Finally, the effects of rainfall and herbivory were examined using linear mixed-effects models of change over time vs the various potential determinants of change using lmer functions in R. Four communities were identified. These communities corresponded well with to the vegetation type descriptions for Western Little Karoo, Little Karoo Quartz Vygieveld and Renosterveld as described in the National Vegetation Map of Mucina and Rutherford (2006). However, the Western Little Karoo was too broad and two communities were recognised within this vegetation type. The finer scale mapping by Vlok et al. (2005) corresponded relatively well to these communities. Results showed an increase in species richness, abundance and cover over time, with the ungrazed plots experiencing more change than the plots exposed to grazing. Most growth forms exhibited an increase in cover, although low leaf succulents declined in both grazed and ungrazed plots. Medium evergreen shrubs declined in the exclosures and stem succulents declined in the grazed plots. The effects were found in both grazed and ungrazed treatments. In addition, many species which declined in abundance were unpalatable or toxic to herbivores. Because of this, the decline in cover of such species was not attributed to grazing, but was instead interpreted as being a response to other disturbance mechanisms, to competitive displacement and to rainfall events. The low stocking rates in the first five years of the study resulted in there being very little difference evident between the treatments. However, once stocking rates increased from 2008, both species richness and cover increased more rapidly in the ungrazed plots, compared to the grazed plots. An increase in palatable and unpalatable species was observed within both ungrazed and grazed plots indicating that grazing did not change the proportion of palatability classes. However, specific plots in the areas of high animal utilisation were more affected as indicated by the response of cover, species richness and palatable species in these specific plots. This suggests that the grazing pressure may be too high within those areas. The linear mixed-effect model supports the argument that grazing pressure is the dominant driver of the community change within grazed plots. Similarly, the results show that rainfall is the primary driver of the vegetation community in the absence of grazing. Timing, amount and intensity of rainfall can mask these impacts. Thus, the contribution of grazing to vegetation change can probably only be detected by tracking the trends over decades or longer. The use of indicators as a management tool is well documented. In order to identify indicators, a theoretical framework for determining indicators species in the different vegetation communities was created. This was based on the correlation between species abundance and sampling period in the different treatments, which identified species that have significantly increased or decreased over time as a result of the change in land use. Species identified as potential indicators were selected on the basis based on their abundance and ranged in lifespans and palatability. The indicators chosen need to be monitored into the future to confirm their utility as indicators. A small but significant difference between grazed and ungrazed plots suggest that herbivore impact is apparent. Identifying this trend indicates that the monitoring programme is providing a useful tool for assessing the impact of herbivores on an ongoing basis. The recovery process following the withdrawal of domestic livestock from Sanbona was much slower in the grazed plots than in the protected plots. Therefore, for the continued recovery of the vegetation to occur and for there to be a sustained increase in cover, active management of animal numbers needs to take place. The results from this study can contribute to future management decisions on the reserve and form a basis for future analyses.